RETRACTED: The Influence of Jakless Planning on Profit Management with Institutional Ownership as a Moderation Ivariable - Regita Syadza Farika; Ahmad Cik; Kumba Digdowiseiso (Journal of Social Science)
The aim of this research is to examine the effect of tax planning on earnings management using institutional ownership as a moderating variable. The data source for this research uses secondary data, the population of this research data is various manufacturing companies in various industrial sectors listed on the Indonesia Stock Exchange (BEI) during the 2015-2020 period. The data sample for this research is 60 samples from 10 companies that carried out Objective Sampling, namely sampling based on certain considerations. Data analysis was carried out using multiple linear statistics processed in SPSS version 25. Based on the results of research conducted using the T-test, it can be concluded that tax planning has no effect on income management and the moderating variable of institutional ownership cannot strengthen the relationship between tax planning and income management.